Winter cover crops effects on soil organic carbon and soil physical quality in a Typical Argiudoll under continuous soybean cropping - Salazar Landea, María Paz (2020)
The massive adoption of no-tillage (NT), along with the simplification of the cropping sequences has led to physical and chemical degradation of soils. To recover degraded soils, cover crops have been proposed as an alternative to increase soil organic carbon (SOC) and to improve soil physical quality (SPQ). This study aimed (i) to determine the content of SOC and its physical and chemical fractions at different layers and positions, in a soil with a soybean crop under NT with and without winter cover crops, and (ii) to determine SPQ indicators in a soybean crop under NT with and without winter cover crops. Measures and samples were made on a field experiment in a typical Argiudoll of the Argentinean Pampas. Soil organic carbon, coarse and fine particulate organic carbon (POCc and POCf), mineral associated organic carbon (MOC), fulvic acids (FA), humic acids (HA), and humins (H) were determined. Soil physical quality indicators determined were: soil bulk density and total porosity from field samples, and saturated hydraulic conductivity, water-conducting macro and mesoporosity, and total porosity connectivity from field water infiltration data. After eight years, cover crops did not cause any observable change in whole SOC content, but significant differences were observed for some SOC fractions. Humic acids and POCc had 40 and 25 % increases, respectively, in the cover crop treatment. Mineral associated organic carbon and H decreased by 9 and 7 % in cover crop treatment. Soil physical quality did not improve after eight years of cover crops. This can be related to degradation processes after 20 years of soybean monoculture under NT, and to the low ability of Argiudolls to recover from physical degradation.